The Mediating Effect of Negative Appearance Evaluation on the Relationship Between Eating Attitudes and Sociocultural Attitudes Toward Appearance - Wang, Ruohang; Gan, Youteng; Wang, Xueyu; Li, Jianye; Lipowska, Małgorzata; Izydorczyk, Bernadetta; Guo, Shuai; Lipowski, Mariusz; Yang, Yin; Fan, Hongying (Frontiers in Psychiatry, 2022)
Objective: Body-image disturbance and eating disorders are significant physical and mental health problems in China. Attitudes toward the body are thought to work in conjunction with other established risk factors for dietary pathology, including body dissatisfaction, dieting, and negative effects. Negative appearance evaluation had the potential to expand work in measuring factors and potential causal relationships associated with body image and eating problems. Therefore, this study aimed was to determine the association of negative appearance evaluation with a combination of eating attitudes and sociocultural attitudes towards appearance, the mediating effect of negative appearance evaluation in the relationship between eating attitudes and sociocultural attitudes towards appearance. Methods: We have invited 339 Chinese people to undergo the Eating Attitudes Test (EAT-26), Fear of Negative Appearance Evaluation Scale (FNAES), and Sociocultural Attitudes Towards Appearance (SATAQ-3), and used AMOS 24.0 for model construction and mediating effects testing. Results: There was a significantly positive correlation of EAT-26 with FNAES (p < 0.001), and SATAQ 3 (p < 0.001) with all dimensions except Internalization general had significant positive correlations (p < 0.05); there was a significant positive correlation between FNAES and SATAQ 3 and all dimensions (p < 0. 01). There was no significant direct effect of eating attitude on sociocultural attitude towards appearance, while there was a significant mediating effect of fear of negative appearance evaluation (β = 0.321, p < 0. 001, 2/df=2.831, AGFI = 0.931, CFI = 0.945, GFI = 0.966, IFI = 0.946, RMSEA = 0.074, SRMR = 0.045, TLI = 0.915). Conclusion: Our results demonstrated that negative appearance evaluation fully mediated the effect between eating attitude and sociocultural attitude towards appearance. An individual's attitude to eating can affect negative body perceptions and therefore their perception of their own body shape. Through the results, we explored the specific effects of eating attitudes on body perceptions and provide a psychological basis for guidance and interventions in Attitudes toward the body.